Implementasi P5 Untuk Mengembangkan Karakter Gotong Royong dan Kreatif Siswa : Implementation of P5 to Develop Students' Mutual Cooperation and Creative Characters - Damayanti, Ni Wayan Siska; Landrawan, I Wayan; Budiarta, I Wayan; Sari, Ketut Siti Amerta; Anjelika, Gst. Ayu Kade Widya (Jurnal IKA, 2025)
This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project (P5) to develop the character of mutual cooperation and creativity in grade XII students at SMAN 1 Bebandem. This study uses a descriptive method with a qualitative approach. This study also uses field research methods, as well as data collection techniques carried out in this study including observation, interviews, and documentation. The subjects of this study are the principal, vice principal for curriculum, project coordinator, project assistant, and grade XII students. The results of this study show that P5 activities have been successful in developing the character of mutual cooperation and creativity in grade XII students at SMAN 1 Bebandem. The theme of the implementation of P5 by class XII is Bhineka Tunggal Ika and Engineering and Technology which consists of mutual cooperation activities to clean the sacred place area and create simple appropriate technology products. In its implementation, class XII gets a time allocation of 6 JP per week. Where 1 JP = 45 minutes.